PENYEDIAAN TANAH UNTUK PEMBANGUNAN JALAN TOL SEMARANG-SOLO TAHAP BAWAEN-SALATIGA PADA MASA PERALIHAN PERATURAN PEMNGADAAN TANAH (PEPRES NO. 65 TAHUN 2006 KE UU NO. 2 TAHUN 2012) - Dhiyas Oga Abitama; Suwanto Adhi; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
The provision of land Semarang-Solo toll road that starts from the third stage BawenhunggaSalatiga occurred during the enactment of the new law on land acquisition, namely Law no. 2 Year 2012. While the Land Procurement Team, as the executor has mengguanakan Presidential Decree no. 65 Taahun 2006 as the basis for the provision of land.This study aimed (1) to demonstrate the process of provision of land development Semarang-Solo toll road Bawen-Salatiga stage when the transition rules for land acquisition and (2) to determine the obstacles that occur in the process of provision of land.This research is implementable with a qualitative approach to collecting data using interview techniques, observation, and documentation. Data analysis using descriptive analysis techniques to describe in detail the situation in the study without manipulating it.This study found that the provision of land at Semarang-Solo toll road Bawen phase-Salatiga still use regulation no. 65 of 2006 due to the provision of land for the Semarang-Solo toll road is a unity although divided into five stages. Keywords : Land Acquisition, Toll Road